Respostas estratégicas dos sindicatos patronais do comércio de bens, serviços e turismo do Brasil às pressões institucionais - Lopez, Daniel Mansur (2012)
The focus of this paper is to identify strategic responses that the trade unions, service and tourism have when submitted to the institutional pressures they face. We used the typology proposed by Oliver (1991), which considers five types of responses, passive agreement of active manipulation. 75 unions were surveyed by a questionnaire that evaluated the pressures which are subject to these unions, which are the main sources of pressures and institutions which the answers provided. Through association maps were related to the responses submitted to the typology proposed by Oliver (1991). The results indicate that the unions surveyed do not have much bargaining power, with main response as reconciliation associated with the tactic of balancing. Another important factor identified, even though to a lesser extent, is the use of the response manipulation with the tactics of influence, so much more active role in that, if encouraged, can generate more power and representation for unions. The implications of this work turn to the programs of strengthening unions undertaken by the National Commerce Confederation for Goods, Services and Tourism (CNC), which must adapt to allow for a more active response capacity of the unions that are part of its scope.